Prevalence and Risk Factors for Complications in Patients with Nontransfusion Dependent Alpha- and Beta-Thalassemia - Poramed Winichakoon (2018)
© 2015 Poramed Winichakoon et al. Background. Nontransfusion dependent thalassemia (NTDT) is a milder form of thalassemia that does not require regular transfusion. It is associated with many complications, which differ from that found in transfusion-dependent thalassemia (TDT). Currently available information is mostly derived from beta-NTDT; consequently, more data is needed to describe complications found in the alpha-NTDT form of this disease. Methods. We retrospectively reviewed the medical records of NTDT patients from January 2012 to December 2013. Complications related to thalassemia were reviewed and compared. Results. One hundred patients included 60 females with a median age of 38 years. The majority (54 patients) had alpha-thalassemia. Overall, 83 patients had one or more complications. The three most common complications were cholelithiasis (35%), abnormal liver function (29%), and extramedullary hematopoiesis (EMH) (25%). EMH, cardiomyopathy, cholelithiasis, and pulmonary hypertension were more commonly seen in beta-thalassemia. Osteoporosis was the only complication that was more common in alpha-thalassemia. The risk factors significantly related to EMH were beta-thalassemia type and hemoglobin < 8 g/dL. The risk factors related to osteoporosis were female gender and age > 40 years. Iron overload (ferritin > 800 ng/mL) was the only risk factor for abnormal liver function. Conclusion. The prevalence of alpha-NTDT complications was lower and different from beta-thalassemia.